4CPS-149 Hospital at home COVID unit: multidisciplinary strategies. (23rd March 2022) - Pires, AM; Brito, A; Alcobia, A
Abstract : Background and importance: The COVID-19 pandemic has had a dramatic impact on worldwide health services. Clinical treatments, hospitalised patient management and the need to guarantee the quality of care for COVID-19 patients were the main challenges. The Hospital at Home (HaH) Unit has already demonstrated efficacy, safety and economic advantage compared to conventional hospitalisation. To reduce the pressure of care in hospitals caused by the pandemic, the HaH COVID Unit was created. Structuring a multidisciplinary team is essential to ensure the best results, reduce mortality and ensure the response in the control of the pandemic. In this sense, pharmacists were involved in developing COVID-19 treatment protocols (C19TP) for patients transferred to the HaH COVID Unit to finish their therapy (corticotherapy and antibiotherapy) at home. Aim and objectives: Characterise C19TP and strategies implemented to optimise medication dispensing for COVID-19 patients. Material and methods: Clinically stable COVID-19 patients were admitted to complete home C19TP between April 2020 and August 2021. On average, medication was dispensed for 5 to 7 days. The developed strategies were: Multidisciplinary cooperation in monitoring COVID-19 patients mostly through telemonitoring and telephone consultations Ensure availability and safe use of drugs Perform protocols for therapeutic management of COVID-19 patients. Results: 165 patients were admitted to the HaH COVID Unit (21 in 2020 and 144 in 2021) to complete the C19TP. The therapy mostly included corticosteroid therapy (28.6% in 2020 and 70.8% in 2021) and antibiotherapy (85.7% in 2020 and 22.9% in 2021), highlighting the recommended therapeutic changes throughout the pandemic. It should be noted that 2 patients completed antiviral therapy with remdesivir at home. Strategic implementation of home visits clearly impacts on the hospital beds' capacity. Conclusion and relevance: HaH COVID Unit is a safe and effective option in carefully selected patients with COVID-19. Collaborative and multidisciplinary management could have a great impact on the improvement of healthcare provided to COVID-19 patients. Pharmacists should actively participate in therapeutic decisions, in the formulation and adjustment of therapeutic regimens for COVID-19 patients, ensuring the monitoring, evaluation of the safety of the medication, efficacy and management of drug interactions. References and/or acknowledgements: 1. Elbeddini et al. Pharmacists and COVID-19. J Pharm Policy Pract 2020;13 :36. Conflict of interest: No conflict of interest